Self-powered wireless smart patch for healthcare monitoring. (February 2017) - Shi, Mayue; Wu, Hanxiang; Zhang, Jinxin; Han, Mengdi; Meng, Bo; Zhang, Haixia
Abstract: Wearable electronics provides an opportunity for everyone to own personal healthcare systems. Convenience, versatility and energy conservation are vital elements to extend the functions of wearable electronics. Here we present a self-powered smart patch with wireless transmission ability based on triboelectric effect and electrostatic induction to monitor the temperature and motion status of individuals. Spontaneous friction charges are utilized to make the system self-powered. The energy and signal are wirelessly transmitted to the receiver through electrostatic induction. The wireless transmission efficiency achieved 26.6% with a 16 cm 2 receiver while the distance is 1 cm, which shows remarkable capability of near-field wireless transmission. With different load resistances from 1 Ω to 1 MΩ, the output current of the receiver keeps constant like a current source. Using a method that transmits energy and signal at the same time, our smart patch can not only collect energy to drive the commercial sensors, but also work as an active sensor monitoring the motion status of people. To realize the wearable electrode, a fabric-based conductor with high stability is developed. A transparent and stretchable silver nanowire (Ag NW) based electrode is fabricated to ensure the compatibility between the receiver and various surfaces such as smartphones. Graphical abstract: In this work, a self-powered wireless smart patch is present to realize wearable wireless transmission utilized for monitoring temperature and motion status without any extra power supply. A novel wireless transmission mechanism based on electrostatic induction is presented showing near field transmission efficiency of 26.6% with distance of 1 cm. Steady fabric based electrodes and stretchable sandwich structural Ag NW electrodes are developed respectively to satisfy the specific demands of convenience and extensive applicability. Highlights: Wireless transmission with high efficiency directly based on triboelectric effect and electrostatic induction was developed. Stretchable and transparent PDMS/Ag NWs/PDMS sandwich structural electrodes are of high compatibility with various surfaces. Highly stable and stretchable CNT/cotton fabric meets the requirements of wearable electronics. Real-time body temperature and motion status monitoring was demonstrated for healthcare application.